IMPROVING LISTENING ABILITY BY ACTIVATING STUDENTS’ BEFORE KNOWLEDGE - Rizal Mulyana Shiddiq; Ridwan Kurniadi; Odo Fadloeli (PROJECT (Professional Journal of English Education), 2019)
This research paper aims at finding whether the students’ ability in listening can be improved by activating students’ previous knowledge. The research was conducted at English education study program of faculty of IKIP Siliwangi Bandung. The research used random sampling class and test by giving pretest and post test. Two classes are experimental class and control class, when the experimental class  got a better score than control class.The experimental class was increased in listening ability. Most of the student’s of experimental class students’ stay in fair category.